Localization of EccA3 at the growing pole in Mycobacterium smegmatis - Nastassja L. Kriel (BMC Microbiology, 2022)
Abstract Background Bacteria require specialized secretion systems for the export of molecules into the extracellular space to modify their environment and scavenge for nutrients. The ESX-3 secretion system is required by mycobacteria for iron homeostasis. The ESX-3 operon encodes for one cytoplasmic component (EccA3) and five membrane components (EccB3 – EccE3 and MycP3). In this study we sought to identify the sub-cellular location of EccA3 of the ESX-3 secretion system in mycobacteria. Results Fluorescently tagged EccA3 localized to a single pole in the majority of Mycobacterium smegmatis cells and time-lapse fluorescent microscopy identified this pole as the growing pole. Deletion of ESX-3 did not prevent polar localization of fluorescently tagged EccA3, suggesting that EccA3 unipolar localization is independent of other ESX-3 components. Affinity purification - mass spectrometry was used to identify EccA3 associated proteins which may contribute to the localization of EccA3 at the growing pole. EccA3 co-purified with fatty acid metabolism proteins (FAS, FadA3, KasA and KasB), mycolic acid synthesis proteins (UmaA, CmaA1), cell division proteins (FtsE and FtsZ), and cell shape and cell cycle proteins (MurS, CwsA and Wag31). Secretion system related proteins Ffh, SecA1, EccA1, and EspI were also identified. Conclusions Time-lapse microscopy demonstrated that EccA3 is located at the growing pole in M. smegmatis. The co-purification of EccA3 with proteins known to be required for polar growth, mycolic acid synthesis, the Sec secretion system (SecA1), and the signal recognition particle pathway (Ffh) also suggests that EccA3 is located at the site of active cell growth.